Analysis Of Regional Tax Potential As A Source Of Regional Original Income In West Nias Regency - Tema Aturai Gulo; Idarni Harefa; Nanny Artatina Bu'ulolo; Serniati Zebua (Jurnal Fokus Manajemen, 2026)
This study aims to analyze the contribution of regional taxes to Local Own-Source Revenue (PAD), measure the effectiveness of tax collection, and assess the extent to which the realization of regional tax revenue reflects the fiscal potential of West Nias Regency. This research employs a descriptive quantitative approach using secondary data obtained from the Regional Financial and Revenue Management Agency (BPKPAD) of West Nias Regency for the 2020–2024 period. The analysis includes the calculation of the contribution of regional taxes to PAD, the effectiveness ratio between realization and target, and the level of fiscal potential reflection (tax gap), using tax targets as an approximation of fiscal potential. The results show that the contribution of regional taxes to PAD falls into the fair category, while the effectiveness of tax collection is very good. The average Fiscal Potential Reflection Level (TPF) of 127.2% indicates that tax realization has optimally reflected the region’s fiscal potential. Overall, the performance of regional tax management in West Nias Regency is categorized as good to very good. The local government is advised to continuously update tax object data, strengthen tax administration systems, and enhance taxpayer awareness to ensure the sustainability of regional revenues and reinforce fiscal independence.